Differences In Characteristics Between Children And Adults In A Descriptive Analysis Of Viral Meningitis With A General Hospital. - Bangash, Sudhair Abbas; Faijue, Darlington David; Rafique, Tariq (Journal of Neonatal Surgery, 2025)
Objectives and introduction: The research shall also be expected to differ in the different ages. Additionally, the research shall also look at the differences in that there is awareness of change that comes with ageing. The constituent parts and the processes served as the location for research that was conducted in retrospect on infectious meningitis cases that required hospitalization due to viral complications. In this study, both the similarities and the differences between the features Children refer to persons below 15 years. The Final Result: During the summer months, the enterovirus is responsible for most cases of viral meningitis in humans. Further, there are more cases of viral meningitis in males than in females during summer. Children are hospitalized in less time than adults whereas children have a shorter length of stay compared to adults. It was determined from the analysis that the disease related to systemic is more severe in children, but. It is important to account for it. Researchers determined that viral meningitis was more common in the environment was males and in summer months since most research findings on medical conditions. The association was made based on medical conditions. The clinical result is shorter in children, and the same was in the presentation and prodrome. All of the CSF findings are lower than the amount of CSF. Since the youngster is analyzed to have had the lumbar puncture before the adult, this is most people. All persons, adults, and children may be infected by the most prevalent types of EV infections